EFEK HEPATOPROTEKTIF EKSTRAK BUNGA ROSELLA(Hibiscus sabdariffa L.) PADA TIKUS PUTIH GALUR WISTARYANG DIINDUKSI ETANOL 20% - Theo Andariaz Zofania, (2020)
Long-term usage and over consumption of alcohol (ethanol) can damage the liver. The damage of liver can be traced through increased levels of SGOT and SGPT which are caused by lipid peroxidation. Antioxidant that are used as neutralizers of lipid peroxidation can use herbal plant such as Roselle which contains flavonoid as antioxidant. The aim of this study is to identify the effects of roselle extracts used towards SGOT and SGPT levels of rats induced by 20% ethanol. A pack of 24 white, male, wistar rats is classified into 6 groups consists of: (1) standard feed and aquades, (2) standard feed and 20% of ethanol orally, (3) Vitamin C, (4) A dose of 250 mg/kgBW/day roselle extract , (5) A dose of 500 mg/kgBW/day roselle extract, and (6) A dose of 750 mg/kgBW/day roselle extract. This study is executed through 30 days which continues with surgery, blood collection from heart , and examination of SGOT and SGPT levels. Data analysis shown using One Way Anova and continued with Post Hoc Bonferonni test. SGOT and SGPT levels were decreased lower on group K6 compared to positive control group. In conclusion, the efficient dose of roselle extract to decrease SGOT and SGPT levels is 750 mg/kgBW/day in rats induced by ethanol 20%